FACTORS AFFECTING THE QUALITY OF THE PADANGSIDIMPUAN GOVERNMENT FINANCIAL STATEMENTS - Meiliana, Putri Bunga (International Journal of Public Budgeting, Accounting and Finance, 2019)
The purpose of this study was to analyse the factors that affect the quality of financial reports in the City Government of Padangsidimpuan. The independent variables in this study are the application of government accounting standards (GAS), the quality of regional government apparatus, utilization of information technology (IT), internal audits and the government's internal control system (GICS), the dependent variable is the quality of reports on regional government performance. The population of this study was 35 units found in the Padangsidimpuan City government. The sample was selected using saturated samples. Data is processed using the SEM method. The results of this study prove that the application of GAS has a significant positive effect on the quality of Padangsidimpuan City's financial statements, the quality of regional government officials has a significant positive effect on the quality of Padangsidimpuan City's financial statements, the use of IT has a significant positive effect on the quality of Padangsidimpuan City financial statements, GISC has a significant positive effect on the quality of the financial statements of the Padangsidimpuan City government. While internal audit has a positive and insignificant effect on the quality of the financial statements of the Padangsidimpuan City government.